Sustainable Utilization of Wudu Water for Fish Farming Through a Community-based Integrated Learning Program in Madrasah Ibtidaiyah - Ai Tusi Fatimah; Tia Setiawan; Lidya Nur Amalia (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
This community service program aims to enhance teacher competence and create innovative learning media at MIS Handapherang by integrating the treatment of water waste ablution with fish farming. The methods used included training, mentoring, and building a functional ablution water installation and piping system to a fish pond. The results showed a significant increase in teacher capacity, evidenced by an average survey score above 4.0 out of 5. Teachers felt more skilled in designing STEAM-H and project-based lesson plans for integrated science and mathematics learning. These lesson plans also improved student engagement and their understanding of water conservation concepts. The project successfully installed environmental values ​​and supported the school's Adiwiyata program. The construction of the fish farming installation served as a physical artifact that transformed waste into a productive resource and a sustainable learning medium. Thus, the program successfully achieved its goal of creating learning innovations with a positive impact on the school environment